Query Language and Query Intent in Cross-Lingual Web Search - Tawfik, Ahmed; Kamel, Ahmed S. (SIGIR 2014 Industry Track, 2014)
This paper examines query intent (or domain) classiﬁcation as a proxy for user information need and its use in improving the performance of cross-lingual information retrieval (CLIR). Through several human relevance studies, information needs that cross language and culture barriers are identiﬁed. Therefore, we propose to use query intent classiﬁers as a ﬁlter to pick queries that may beneﬁt from CLIR. The analysis presented in this paper are based on experiments conducted on three populations with a high percentage of bilingual internet users: the Arabs, the French Canadians, and Spanish speakers in the US. While these users diﬀer signiﬁcantly in their usage of search engines, the eﬀect of CLIR on the quality of the search experience for individual intents was largely similar. This leads us to expect a wider applicability of our ﬁndings on a global scale.